CASE REPORT : MYIASIS CLINICAL TREATMENT OF 2 MONTH OLD DAIRY CALF - Saraswati, Nabila Ayu (VITEK : Bidang Kedokteran Hewan, 2024)
This case study reports the treatment of a 2 month old dairy calf that has myiasis on its right hind leg. The myiasis was first noticed by the farm that stated the calf had an open wound with maggot infestation and a noticeable foul odor. On examination, the calf limping due to an open wound. Clinical examination palpation was performed and there was obvious pain in the wounded area followed by high body temperature, and rapid heart rate. Treatment consists of removing maggots from the wound, cleaning the wound site with H2O2, Rivanol®, and diluted povidone iodine. Debridement of the wound by excising the edges of the injured skin with a scalpel was done to expose surrounding healthy tissue. Antibiotic powder applied to the wound before suturing. Wound suturing was done with simple interrupted sutures with 2.0 silk sutures. After suturing process was completed, injection of Intramox®, Biopros®, and Dexapros® was given for 3 days. Then followed by oral antibiotics Sulfapros® until day 7. External wound care was done with regular monitoring and spraying of Intra Repiderma® for 21 days. The prognosis was good and suture removal performed 5 days after the procedure.